PENINGKATAN MANAJEMEN KESEHATAN TERNAK DALAM MENINGKATKAN EFISIENSI TERNAK MASYARAKAT DESA ABEKO KECAMATAN RANOMEETO BARAT KABUPATEN KONAWE SELATAN - Takdir Saili; Sahindomi Bana; Rusli Badaruddin; Syamsuddin Syamsuddin; Purnaning Dhian Isnaeni (Universitas Halu Oleo, 2021)
Diseases are the disadventages in livestock farming that must be overcame with good animal health management practices. Animal health management must be implemented to improve livestock productivities. Farmers on Abeko Village, Ranomeeto Barat Sub-District, Konawe Selatan are still uninformed about the importance of animal health management practices. This programme aimed to improve the farmers’ knowledge and understanding in maintaining animal health in order to gain maximum livestock production. The methods used in this program were physical and non-physical activities such as restraining box construction, animal health treatment, discussion, and counseling.